PENERAPAN FLIPPED CLASS LEARNING DALAM PEMBELAJARAN IPS SMPN 16 MALANG - Siti Ismi Nur Azizah; Listyo Yudha Irawan; Siti Ismi Nur Azizah (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Abstract: The purpose of applying this flipped class learning model is to facilitate students and provide innovation to teachers in the learning process. The strategy of implementing this activity uses the methods used, including lectures, discussions, literature studies. The results obtained in this activity make grade IX-G students of Junior High School 16 Malang in social studies learning have sufficient provisions in creating effective classes using a Flipped Class Learning (FCL) learning model. The benefits arising from all activities carried out in this article are described through direct and indirect benefits..